Injury rates and characteristics in recreational, elite student and professional dancers: A systematic review - Vassallo, A. J.; Trevor, B. L.; Mota, L.; Pappas, E.; Hiller, C. E. (Journal of Sports Sciences, 2019)
The purpose of this study was to systematically review the literature and synthesise the evidence on injury rates and characteristics in recreational, elite student, and professional dancers. Five online databases were searched from inception to January 2018 and screened by two independent reviewers. Primary research studies were eligible for inclusion if they reported injury rates in recreational, elite student, and/or professional dancers of any genre and measured individual dance exposure at the hour, event, or day level. Sixteen studies were included, with only three studies incorporating recreational dancers. Reported injury incidence rates were less than 5 injuries per 1,000 dance hours, however substantially different definitions and methods for measuring injury and dance exposure were used. Based on the current evidence there is not an identifiable difference in injury rate or characteristics between recreational, elite student, and professional dancers. However, there remains a lack of high quality comprehensive data available across levels and genres of dance participation, and greater focus on consistency and completeness of reporting in dance injury research is still required.